The role of gut leakage and immune cell miss-homing on gut dysbiosis-induced lung inflammation in a DSS mice model - Mariam Wed Eladham; Narjes Saheb Sharif-Askari; Priyadharshini Sekar; Bushra Mdkhana; Balachandar Selvakumar; Baraa Khalid Salah Al-Sheakly; Fatemeh Saheb Sharif-Askari; Ibrahim Hachim; Rabih Halwani (PLoS ONE, 2025)
Background Inflammatory Bowel Disease (IBD), encompassing Crohn’s disease and ulcerative colitis, affects millions globally, with extraintestinal manifestations (EIMs) occurring in 25–40% of patients. Among these, respiratory complications are of particular concern, yet the immunologic and physiologic mechanisms underlying gut-lung interactions remain poorly understood. The gut-lung axis (GLA) describes bi-directional communication between the gut and lungs, where microbial dysbiosis in the gut can drive lung inflammation and immune dysregulation. Methods Mice were treated with 4% DSS for 7 days to induce colitis. Gut permeability, tight junction protein expression, lung inflammation, immune cell trafficking, and microbial translocation were assessed through histology, qPCR, flow cytometry, and GFP-tagged fecal microbiome experiments. Results DSS treatment led to significant disruption of the gut barrier, with upregulation of gut leakage markers and downregulation of tight junction proteins. Lung inflammation was characterized by elevated IL-17, neutrophil infiltration, and airway hyperresponsiveness. Flow cytometry revealed mis-homing of gut-primed immune cells (α4β7+ and CCR9 + CD4+) to the lungs and tracking bacteria via GFP- tagged fecal microbiome confirmed microbial translocation from the gut to the lungs which may contribute to lung inflammation. Conclusion Disrupted gut integrity facilitates microbial translocation and immune cell mis-homing, contributing to lung inflammation. These results provide new insights into how gut dysbiosis influences respiratory inflammation.